2022
DOI: 10.3390/antiox11112120
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 and Ischemic Stroke: A Narrative Review

Abstract: Ischemic stroke is one of the major causes of death and permanent disability worldwide. The only efficient treatment to date is anticoagulant therapy and thrombectomy, which enable restitution of blood flow to ischemic tissues. Numerous promising neuroprotectants have failed in clinical trials. Given the complex pathomechanism of stroke, a multitarget pharmacotherapy seems a more rational approach in stroke prevention and treatment than drugs acting on single molecular targets. Recently, vitamin D3 has emerged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 162 publications
1
7
0
Order By: Relevance
“…In addition, multivariate regression analysis based on these cut-offs revealed significant associations with lower serum Vit D levels. These results are consistent with those of previous studies that demonstrated an association between Vit D deficiency and poor short-term post-stroke functional outcomes [11,14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, multivariate regression analysis based on these cut-offs revealed significant associations with lower serum Vit D levels. These results are consistent with those of previous studies that demonstrated an association between Vit D deficiency and poor short-term post-stroke functional outcomes [11,14].…”
Section: Discussionsupporting
confidence: 93%
“…Infectious complications such as post-stroke pneumonia have been associated with Vit D deficiency [13]. Vit D levels affect stroke recurrence and functional outcomes [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the extensive literature on this topic does not seem to link neither Vitamin D nor the higher dosage regime to cerebral infarction as in this instance. While researchers consider vitamin D deficiency to be associated with ischemic stroke risk, severity, and prognosis (Alharbi et al, 2022), vitamin D3 supplementation, on the other hand, appears to prevent and improve the neurological and psychiatric effects of ischemic stroke (Lasoń et al, 2022).…”
Section: Safety Of Vitamin D Supplementationmentioning
confidence: 99%
“…The non-genomic pathways are rapid compared to the genomic response and are mediated through specific membrane receptors like VDR and PDIA3 (protein disulfide isomerase family A member 3) (Figure 2). VDR interacts with various target proteins such as β-catenin, c-Jun, STAT1, inhibitor of nuclear factor-κB (IκB) kinase (IKK), cAMP response element-binding protein, and Runt-related transcription factor 1 (RunX 1) in the non-genomic response in vitro [76,77].…”
Section: Non-genomic Action Of Calcitriolmentioning
confidence: 99%